Tingkat Pengetahuan Publik (Public Knowledge) Terhadap Penyakit Hewan Menular Strategis Rabies Dalam Upaya Mendukung Status Lombok Bebas Rabies - Made Sriasih; Sulaiman Ngongu Depamede; Muhammad Ali; Wayan Wariata; Answar Rosyidi (Universitas Mataram, 2020)
Rabies is one of strategic infectious animal diseases that attacks the central nervous system. Rabies is very widespread and is found in nearly 150 countries and regions on all continents, except Antarctica. Although West Nusa Tenggara is one of the nine provinces in Indonesia that is free of rabies, the number of dog bite victims reported on the island of Sumbawa with 32 samples of rabies-carrying animal brains identified as positive in early 2019 indicates the need to increase awareness of rabies transmission to Lombok Island. Increasing public knowledge which includes parents and students at primary school, elementary school and high school about rabies through surveys, counseling and demonstration is one of the efforts to prevent and control rabies. The results showed that the extension activities were able to increase participants' knowledge. High school students had the best level of knowledge (97.5% ± 2.08) when compared to the elementary school participants (93% ± 3.56) and elderly respondents (88.75% ± 4.79) of all indicators of knowledge about rabies. The combination of extension activities with hands-on practice has had a positive effect on increasing public knowledge about rabies